A closed-loop feature-based FTS patterning and characterisation of functional structured surfaces. (21st April 2021) - Tong, Zhen; Zeng, Wenhan; Zhong, Wenbin; Jiang, Xiangqian
Abstract: To improve the feasibility and efficiency of ultra-precision surface structuring, a closed-loop fast-tool-servo (FTS) surface patterning and measurement system is developed with functional modules of feature-based tool path generation, embedded surface measurement and integrated surface characterisation toolkit. A dedicate controller HUDCNC is developed for the process control of FTS surface patterning and on-machine surface measurement (OMSM). Algorithms are developed for data formatting and transformation of designed patterns into the FTS cutting points (maximum number of 5 million points). The feasibility and performance of the proposed closed-loop FTS machining system are demonstrated by successfully generating typical functional structured surfaces including periodic structures, patterns and tessellations, biological surfaces, profile and character combinations. The results indicate that the feature-based FTS patterning and surface characterisation system provides a promising solution to the design and manufacturing of high-precision functional structured surfaces. The integrated OMSM system and the surface characterisation toolkit allow the fast inspection and quality control of the machined functional surfaces.